Analisis Perilaku Anak Pecandu Game Mobie Di Kelurahan Harjosari I Kecamatan Medan Amplas - Bagus Prayugo; Euis Aisyah; Wulan Dayu; Imam El Islamy (Pusat Studi Gender dan Anak, 2022)
This article is based on research conducted on children in the Harjosari 1 sub-district, Medan Amplas sub-district on the behavior of mobile game addiction. This article aims to see how much influence online games have on children. It was found that children who are addicted to mobile games who play more than 5 hours a day will change their behavior to become more violent and often speak harshly. That's due to the emotional state of children who tend to be unstable due to losing games. As well as the rude behavior of children who are ordered from the game being played. Overall, mobile games are not dangerous if done at the right time and not excessive because online games can grow children's sensory to become more sensitive and aware. The method used in this article is a mix method, the author combines qualitative and quantitative approaches. The method of data collection is direct observation related to the object of research. Closed interview, which is asking a list of questions and also a documentation study by looking at references related to research